Pemodelan Rantai Markov dalam Memprediksi Hasil Panen Kopi di Pulau Sumatera - Hasibuan, Eka Sri Hartini; ameliya, Ameliya; Annisa Hidayah; Piliang, Yumna Khairi Amani; Manullang, Sudianto; Nasution, Alvi Sahrin (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Coffee is one of the leading commodities in Indonesia, especially in the Sumatra Island region. The provinces of Aceh, North Sumatra, West Sumatra, South Sumatra, Bengkulu, and Lampung are the main centers of coffee production, both Arabica and Robusta types. In addition to being the main source of income for farmers, coffee also plays an important role in supporting the country's foreign exchange. However, coffee production in the region still faces various challenges, such as climate fluctuations, erratic rainfall, pest attacks, and variations in cultivation techniques that cause instability in harvest yields from year to year. This study aims to predict coffee harvest yields during the period 2024 to 2028 using the Markov Chain model. This model is used to describe the shift in production distribution between provinces based on the transition probability from previous conditions. The data used are secondary data on coffee harvests from 2018 to 2023. The analysis was carried out by compiling a transition matrix, calculating the probability distribution for each year, and estimating the harvest yield quantitatively. The prediction results show a relatively stable annual production of around 538 thousand tons. The Mean Absolute Percentage Error (MAPE) value of 9.93% indicates a fairly good level of model accuracy. In addition, steady state conditions are estimated to be achieved in 2030. This study contributes to efforts to formulate adaptive and sustainable coffee distribution and production planning policies in Sumatra. Abstrak. Kopi merupakan salah satu komoditas unggulan di Indonesia, khususnya di wilayah Pulau Sumatera. Provinsi Aceh, Sumatera Utara, Sumatera Barat, Sumatera Selatan, Bengkulu, dan Lampung menjadi sentra utama produksi kopi, baik jenis Arabika maupun Robusta. Selain menjadi sumber utama pendapatan petani, kopi juga berperan penting dalam menopang devisa negara. Namun, produksi kopi di wilayah tersebut masih menghadapi berbagai tantangan, seperti fluktuasi iklim, curah hujan yang tidak menentu, serangan hama, dan variasi teknik budidaya yang menyebabkan ketidakstabilan hasil panen dari tahun ke tahun. Penelitian ini bertujuan untuk memprediksi hasil panen kopi selama periode 2024 hingga 2028 dengan menggunakan model Rantai Markov. Model ini digunakan untuk menggambarkan peralihan distribusi produksi antar provinsi berdasarkan probabilitas transisi dari kondisi sebelumnya. Data yang digunakan merupakan data sekunder hasil panen kopi dari tahun 2018 hingga 2023. Analisis dilakukan dengan menyusun matriks transisi, menghitung distribusi probabilitas tiap tahun, serta memperkirakan hasil panen secara kuantitatif. Hasil prediksi menunjukkan produksi tahunan yang relatif stabil, sekitar 538 ribu ton. Nilai Mean Absolute Percentage Error (MAPE) sebesar 9,93% menunjukkan tingkat akurasi model yang cukup baik. Selain itu, kondisi steady state diperkirakan tercapai pada tahun 2030. Penelitian ini memberikan kontribusi dalam upaya penyusunan kebijakan distribusi dan perencanaan produksi kopi yang adaptif dan berkelanjutan di Sumatera.